Amostragem sequencial e microssatelites na avaliação da qualidade genética em lotes de sementes de milho - Lopes, Magnólia de Mendonça [UNESP]; Vieira, Maria das Graças Guimarães Carvalho (My University, 2014)
In the seed production system, genetic purity is one of the fundamental requirements for its commercialization. The present work had the goal of determined the sample size for genetic purity evaluation, in order to protect the seed consumer and the producer and to evaluate the sensitivity of microsatellite technique for discriminating hybrids from their respective relatives and for detecting mixtures when they are present in small amounts in the samples. For the sequential sampling, hybrid seeds were marked and mixed in with the seed lots, simulating the following levels of contamination: 0.25, 0.5, 1.0, 2.0, 4.0, and 6.0%. After this, groups of 40 seeds were taken in sequence, up to a maximum of 400 seeds, with the objective of determining the quantity of seeds necessary to detect the percentage of mixture mentioned above. The sensitivity of microsatellite technique was evaluated by mixing different proportions of DNA from the hybrids with their respective seed lines. For the level of mixture was higher than 1:8 (1P1:8P2; 8P1:1P2), the sensitivity of the marker in detecting different proportions of the mixture varied according to the primer used. In terms of the sequential sampling, it was verified that in order to detect mixture levels higher than 1% within the seed lot- with a risk level for both the producer and the consumer of 0.05- the size of the necessary sample was smaller than the size needed for the fixed sample size. This also made it possible to reduce costs, making it possible to use microsatellites to certify the genetic purity of corn seeds lots.
Sequential sampling and microsatellites for evaluation of the genetic quality in corn seeds lots
Keywords: DNA; Genetic purity; Hybrids; Zea mays